European Electronic Personal Health Records initiatives and vulnerable migrants: A need for greater ethical, legal and social safeguards. Issue 1 (1st August 2019) - Feeney, Oliver; Werner‐Felmayer, Gabriele; Siipi, Helena; Frischhut, Markus; Zullo, Silvia; Barteczko, Ursela; Øystein Ursin, Lars; Linn, Shai; Felzmann, Heike; Krajnović, Dušanka; Saunders, John; Rakić, Vojin
Abstract: The effective collection and management of personal data of rapidly migrating populations is important for ensuring adequate healthcare and monitoring of a displaced peoples' health status. With developments in ICT data sharing capabilities, electronic personal health records (ePHRs) are increasingly replacing less transportable paper records. ePHRs offer further advantages of improving accuracy and completeness of information and seem tailored for rapidly displaced and mobile populations. Various emerging initiatives in Europe are seeking to develop migrant‐centric ePHR responses. This paper highlights their importance and benefits, but also identifies a number of significant ethical, legal and social issues (ELSI) and challenges to their design and implementation, regarding (1) the kind of information that should be stored, (2) who should have access to information, and (3) potential misuse of information. These challenges need to be urgently addressed to make possible the beneficial use of ePHRs for vulnerable migrants in Europe.